A short review on production of syngas via glycerol dry reforming - Sumaiya, Zainal Abidin @ Murad; Asmida, lderis; Nurul Aini, Mohamed Razali; Mazni, Ismail (2019)
Glycerol. a by-product from biodiesel production, has been widely investigated as one of the alternative feedstocks for production of synthesis gas (syngas). The production of syngas through glycerol pyrolysis, gasification, and steam reforming has been well established. However, to date, there were only a few literatures focusing on the use of glycerol dry reforming (GDR) to produce syngas. GDR offers a better pathway for the production of syngas as it converts carbon dioxide, a greenhouse gas, into a value-added product and converts the biodiesel by-product, glycerol, into an alternative source of energy. Nickel (Ni) is extensively used as a catalyst in many reforming processes due to its excellent capacity for carbon-carbon bond cleavage and because it is easily available and economically cheap. The major challenge faced by the application of Ni as a catalyst in GDR is mainly due to the deactivation of catalyst through carbon formation. This review focuses on the performance of potential catalysts and operating conditions that exhibit high catalytic activity and stability in GDR. Few perspectives of catalyst properties such as catalyst dispersion, basicity and acidity, reducibility, oxygen storage capability, and interaction between support and catalyst have been included in the review, and their catalytic performances have been deliberated. Effects of reaction parameters such as reaction temperature, gas hourly space velocity, and reactants partial pressure were discussed in detail, followed by the thermodynamics study. This short review is expected to create a clear understanding on the correlation between catalytic properties and their performance in glycerol dry reforming.